Hadis-Hadis Jihad: dari Humanisme Menuju Kekerasan Agama - Sefriyono, Sefriyono; Ilhamni, Ilhamni; Rahmi, Rahmi (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Radicalism exists in every religion, including Islam. There are various motives of the perpetrators to carry out radical actions, one of which is literal religious knowledge, such knowing the hadith. Radicals subscribe to an essentialist or primordialist worldview when it comes to comprehending religious teaching in the context of societal violence. They view religious conflict as a natural part of religion. This essay aims to investigate the radical potential of the jihad hadiths. The author also examines how radical organizations figuratively construct this potential to support their violent actions. This study finds that literal interpretation of jihadist hadiths frequently serves as a catalyst for religious violence. It does this by applying qualitative approaches to hadith literature. Jihad is only understood as battle in this context (qitaal). The humanist interpretation of the hadith of jihad, which can imply a commitment to maintain truth and justice, is negated by this literal interpretation.